Magneto‐Electric Directional Anisotropy in Polar Soft Ferromagnets of Two‐Dimensional Organic–Inorganic Hybrid Perovskites. Issue 26 (24th May 2021) - Taniguchi, Kouji; Nishio, Masaki; Abe, Nobuyuki; Huang, Po‐Jung; Kimura, Shojiro; Arima, Taka‐hisa; Miyasaka, Hitoshi
Abstract: Two‐dimensional organic–inorganic hybrid perovskites (2D‐OIHPs) are attracting interest due to their structural tunability and rich functional characteristics, such as ferroelectricity and ferromagnetism. Here, we report the chiral‐polar ferromagnetic 2D‐OIHP copper chlorides with discernable electric polarization in the inorganic layers. In these systems, the magneto‐electric (ME) correlation has been clearly observed by measuring a magneto‐electric directional anisotropy (MEA), in which an optical absorption coefficient changes with reversal of the light propagating direction. We have found that the MEA can be induced by a low magnetic field of about 50 mT, reflecting soft magnetic nature. The present results suggest a new paradigm for designing functional ME multiferroics, which effectively couples magnetic and electric properties. Abstract : Magneto‐electric (ME) correlation in two‐dimensional organic–inorganic hybrid perovskites (2D‐OIHPs) is demonstrated with a polar soft ferromagnetic system for the first time. The polarity of 2D‐OIHPs is found in the nonmagnetic organic layers and also in the magnetic inorganic layers, where the ME response should be induced. Reflecting the soft magnetic nature, the ME‐response is achieved by a low magnetic field.